2000
DOI: 10.1002/jlb.67.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclooxygenase-2 by human monocytes exposed to group B streptococci

Abstract: Group B streptococcal (GBS) infections are associated with high morbidity and mortality. The molecular pathways mediating the pathophysiological events in GBS infection are not fully delineated. Cyclooxygenases (COX) are the enzymes that convert arachidonate to active eicosanoids. To identify the effects of GBS on eicosanoid metabolism and regulatory mechanisms, we exposed human monocytes to GBS and found that they secreted prostaglandin E 2 , prostacyclin, and thromboxane A 2 . Exposure to GBS caused monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Consequently, it is time-consuming, laborious and hardly feasible in routine clinical practice, as treatment is usually started without prior platelet function testing. In our study, the vast majority of patients received endothelium, may contribute to the observed association [34][35][36] . The weaker impact of inflammation on serum TXB2 also supports the assumption that extraplatelet sources play a role in the strong correlation between inflammation and urinary D-TXB2.…”
Section: Supplementary Tablementioning
confidence: 61%
“…Consequently, it is time-consuming, laborious and hardly feasible in routine clinical practice, as treatment is usually started without prior platelet function testing. In our study, the vast majority of patients received endothelium, may contribute to the observed association [34][35][36] . The weaker impact of inflammation on serum TXB2 also supports the assumption that extraplatelet sources play a role in the strong correlation between inflammation and urinary D-TXB2.…”
Section: Supplementary Tablementioning
confidence: 61%
“…Early-onset GBS pneumonia is characterized by presence of numerous bacteria, an inflammatory exudate, and marked pulmonary epithelial and endothelial cell injury (1,10). Innate proinflammatory responses to GBS infection which may contribute to the respiratory pathology include the synthesis and release of cytokines (12,22), prostaglandins (16), and nitric oxide (NO) (6,15).…”
mentioning
confidence: 99%
“…Effective first-line defense must be established in the earliest stages of microbial invasion, before the microbial sensing system is overwhelmed by large numbers of invading bacteria (Medzhitov and Janeway, 2000). At the same time, innate proinflammatory response to GBS infection may contribute to bacterial pathology through the synthesis and release of cytokines, prostaglandins and nitric oxide (Kwak et al, 2000;Leib et al, 1998;Maloney et al, 2000). It appears therefore that the virulence of different strains may be due not only to different genotypes but also to the induction of different amounts of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%